Law Enforcement of Corruption Crimes by Village Apparatuses in Village Fund Allocations - Wibowo, Dava Prawira; Aqil, Muhammad Zumri (Faculty of Law, Universitas Lampung, 2023)
Indonesia is still struggling to break free from the shackles of corruption. Corruption does not only occur at the central government level, but corruption also occurs at the village government level. Such a large source of village funding is a consequence of the enactment of the Village Law Number 6 of 2014. The Village Fund (DD) is very likely to become a wetland for village officials/officials to commit acts of corruption. That with very large village funds, it is possible that many village officials take advantage of their power to commit fraud and others The method used by using a normative juridical approach method and supported by empirical juridical approach in the form of support from criminal law experts and law enforcement to support normative juridical data. Approach Normative juridical is done by seeing, analyzing and interpreting matters of a theoretical nature concerning legal principles through search related literature directly or indirectly direct In an effort to tackle the criminal act of corruption in village funds, it CAN be carried out in 2 (two) ways, the first effort is a preventive or non-penal effort. related agencies to carry out investigative audits. The prosecutor can do pro justitia. After conducting the audit, the prosecutor's office wrote to the relevant party, namely the alleged party, in this case the village official, to return the money within 60 days starting from the letter received by the alleged party. If within 60 days the alleged party does not return the money, the prosecutor's office will take repressive v action. in making efforts to overcome criminal acts of corruption, funds should be more inclined to seek repressive measures, although not forgetting that preventive measures themselves are based on pro justitia or have binding legal force.